If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 9 = 2 + 3x + -2x Combine like terms: 2 + 9 = 11 11 = 2 + 3x + -2x Combine like terms: 3x + -2x = 1x 11 = 2 + 1x Solving 11 = 2 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 11 + -1x = 2 + 1x + -1x Combine like terms: 1x + -1x = 0 11 + -1x = 2 + 0 11 + -1x = 2 Add '-11' to each side of the equation. 11 + -11 + -1x = 2 + -11 Combine like terms: 11 + -11 = 0 0 + -1x = 2 + -11 -1x = 2 + -11 Combine like terms: 2 + -11 = -9 -1x = -9 Divide each side by '-1'. x = 9 Simplifying x = 9
| 4(6a+6)=-8(-5a-9) | | 2(x-1)=2(x-1) | | 2.25x+4.50=1.75x+6 | | 8s-16-5s=-5 | | 10-x=3(x-6) | | 6-a/3=2 | | 6+2.5+6+2.5= | | 0.7x+0.6(12-x)=47 | | 7+4p=19 | | F(h(x))=x^2+7 | | V-4=5+5v+3 | | 29=-9v+9-v | | -9m-3=78 | | 5+x-4x=-1 | | 8x-2(3x-5)=3x+15 | | -3-8x=-10-2x-7x | | 2x-5(x-4)=-3+4x-12 | | -6b-8=19 | | 4g-6-9=3 | | 3=5-2a | | 8x-1=8(x-3) | | 5x+8(-4x-9)=-10(-2x-9)+26 | | x^2-6x-96=0 | | 2k-1=-5+3k | | 24x=24+7x | | -3(4p+4)-2(6-14p)-3(7+5p)=0 | | 2(-5U+10)+2u= | | 2-5a=-8 | | 7x+5x-38=95-7x | | 2k-1=-5+2k | | 5b-13=3b+1 | | t=6s+18.01 |